Potensi Pemanfaatan Limbah Isi Rumen Sapi Untuk Meningkatkan Produksi Tanaman (Studi Pada Tanaman Terung Solanum melongena L.) - Wijayanto, Teguh; Kandari, Aminuddin Mane; Darmawansyah, Darmawansyah (PROSIDING SEMINAR NASIONAL AGRIBISNIS, 2015)
Rumen’s animal waste is usually abundant in quantity.  The rumen is not only a store house of microbes that assist in the digestion of roughage in ruminant animals but it is also an important source of nutrient for crop plant. This study aimed to determine the effect of cow’s rumen waste on eggplant crop production. The study consisted of a single factor, the application of cow’s rumen contents, with 6 treatment levels, namely: R0 = Control (without giving cow's rumen); R1 = 5 tons cow’s rumen per hectare (3.6 kg per plot); R2 = 10 tons of cow's rumen per hectare (7.2 kg per plot); R3 = 15 tons of cow's rumen per hectare (10.8 kg per plot); R4 = 20 tons of cow's rumen per hectare (14.4 kg per plot); R5 = 25 tons of cow’s rumen per hectare (18 kg per plot); and R6 = 30 tons of cow’s rumen per hectare (21.6 kg per plot). The study was based on Complete Randomized Block Design (CRBD), which consisted of three blocks, so overall consisted of 21 experimental units. The results showed that the application of cow's rumen waste gave a very significant effect on the weight of eggplant fresh fruit, fruit diameter, fruit number, and gave significant effect on fruit length. The application of cow’s rumen with a dose of 25 tons per hectare (18 kg per plot) resulted in the highest agronomic results for eggplant production, which was 28.85 tons per hectare, or equivalent to 20.77 kg per plot. But economically, rumen dose of 15 tons per hectare (10.8 kg per plot) has given the best results, with production per hectare of 21:39 tons, or equivalent to 15.4 kg per plot.